Del parir a la violencia obstétrica en México: acontecimiento y problema público - Alicia Márquez Murrieta (Antípoda: Revista de Antropología y Arqueología, 2023)
By publishing cases of women giving birth outside public hospitals, on grass or sidewalks in Mexico, something that I refer to as an event in the article, I analyze the growing public discussion around obstetric violence in the country. I am interested in observing how an event that took time to unfold became linked to a public issue, in this case, obstetric violence. Through this linkage, specific dimensions of said issue (particularly discrimination) became visible, and once associated with the event, the topic of obstetric violence also gained strength and public visibility. In Mexico, discussion surrounding the issue began in the first decade of the 21st century, but the debate began to be more widespread in the second decade of the 21st century. In the article, I explore the connection between the published accounts of women giving birth outside public hospitals, cases that are analytically understood as events, and obstetric violence as a public issue. The analysis includes journalistic articles from both traditional press and digital platforms (Facebook), as well as press releases and communiqués from social organizations that have been involved in reproductive health issues for decades. These documents have also been made public through various media outlets. I argue that while the public issue of obstetric violence had been ongoing in Mexico for some years, its thematic exploration through these specific cases amplified the visibility and discussion of obstetric violence as a situation experienced by indigenous women in areas with limited access to adequate healthcare services. The novelty of the article lies in its linkage of two theoretical domains – the realm of events and that of public issues. This approach illuminates specific ways in which obstetric violence is discussed, enhancing the overall understanding and visibility of the topic.